Phenotypic and transcriptomic responses of diverse rice accessions to transient heat stress during early grain development - Nalini Chandran, Anil Kumar; Paul, Puneet; Dhatt, Balpreet K.; Sandhu, Jaspreet; Irvin, Larissa; Oguro, Shohei; Shi, Yu; Zhang, Chi; Walia, Harkamal (Frontiers in Plant Science, 2024)
Heat stress (HS) occurring during the grain-filling period has a detrimental effect on grain yield and quality in rice (Oryza sativa). The development of heat-resilient cultivars could partly solve this issue if tolerant alleles can be identified and incorporated into the germplasm. In this study, we posit that some of the phenotypic variations for heat resilience during grain development could be due to variations in gene expression among accessions. To test this, we characterized the HS response of 10 diverse rice accessions from three major sub-populations using physiological and transcriptome analyses. At a single-grain level, grain width and grain thickness emerged as the most heat-sensitive traits. During a transient HS, IND-3 was categorized as highly sensitive, while five accessions exhibited moderate heat sensitivity, and four accessions were tolerant. Only a core set of 29.4% of the differentially expressed genes was common to the three rice sub-populations. Heat-tolerant accession TEJ-5 uniquely triggered an unfolded protein response (UPR) under HS, as evident from the induction of OsbZIP50 and downstream UPR genes. OsbZIP58, a gene that positively regulates grain filling, was more highly induced by HS in IND-2 despite its moderate heat sensitivity. Collectively, our analysis suggests that both unique gene expression responses and variation in the level of responses for a given pathway distinguish diverse accessions. Only some of these responses are associated with single-grain phenotypes in a manner consistent with the known roles of these genes and pathways.